Close to the border-Resilience in healthcare in a European border region: Findings of a needs analysis. - Leonie A K Loeffler; Sophie Isabelle Lambert; Lea Bouché; Martin Klasen; Saša Sopka; Lina Vogt; COMPAS Consortium (PLoS ONE)
Objectives Promoting resilience, the ability to withstand and overcome challenging situations, is crucial for maintaining the performance of healthcare systems. Unique challenges faced by healthcare facilities in border regions render them particularly vulnerable during crises, emphasizing the need to promote resilience in these areas. The current study evaluated the state and needs of resilience in healthcare professionals in a representative European border region. Methods All hospitals and emergency medical care services in the Euregio Meuse-Rhine (Germany, Belgium, the Netherlands) were approached to participate via an online-survey. Behavioral data on psychological distress (Patient Health Questionnaire-4), work-related stressors, individual resilience (Brief Resilience Scale, Resilience at Work scale), and organizational resilience (Benchmark Resilience Tool-short) were collected. Results 2233 participants initiated the survey with 500 responses included in the analysis. 46% of the participants indicated clinically significant psychological distress. Most challenging stressors were staff availability, available time, and workload. On average, individual resilience was in the normal range, yet 15.6% showed below average resilience. At the organizational level, healthcare institutions can particularly enhance resilience in the domains of Internal resources, Situation Awareness, and Unity of purpose. Compared to their neighbor countries, German healthcare professionals indicated higher levels of depressive symptoms, were more burdened by work-related stressors, and reported lower levels of organizational resilience. Conclusion Findings highlight that healthcare institutions not only need to promote the resilience of the individual employee particularly in border regions, healthcare institutions, must also act to be better prepared for potential threats and crises while considering each country's unique needs.